Development Prototype of Smart Mailbox That Send Email to User When Parcel Barcode Being Scanned - Mohamed Firdaus, Mohamed Fakhruzzaman; Kamarudin, Kamarul-azhar (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The rise of internet usage worldwide has created a new phenomenon of consumer behaviour, in which the consumers’ attention has been shifted to online purchasing. Lots of courier recruit part time delivery workers and paid by commission based depend total parcel they send. Because of this commission based earning, often courier will throw customer parcel or left parcel near the house’s gate if no one come out to pick up the parcel. These situations will lead to missing parcel and parcel being stole. This project will focus on developing a smart mailbox’s system that send email to user when parcel’s barcode being scanned. The project will use Arduino Uno as the microcontroller and the smart mailbox will be fabricate using aluminium and acrylic. With help of smart mailbox’s system, parcel delivery can be done faster than before. This is because courier do not need to wait for customer to come out and take their parcel. In future, smart mailbox can be improve more on safety such as use locking system.